2011
DOI: 10.1002/jor.21454
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite therapy as a more efficacious and less inflammatory alternative to bone morphogenetic protein‐2 in a rodent arthrodesis model

Abstract: The use of recombinant human bone morphogenetic protein-2 (rhBMP-2) in spine fusion has led to concerns regarding a potential accompanying inflammatory response. This study evaluates a combination therapy (TrioMatrix 1 ; Pioneer Surgical, Inc., Marquette, MI) comprised of a demineralized bone matrix (DBM), hydroxyapatite, and a nanofiber-based collagen scaffold in a rodent spine fusion model. Thirty-six athymic rats that underwent a posterolateral intertransverse spinal fusion were randomly assigned to 1 of 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…Of note, a negative control group was not used, as ACS alone has previously demonstrated a 0% fusion rate and thus serves as a historical control. 12,18 Radiographic fusion was evaluated 4 and 8 weeks postoperatively. Spines were harvested at 8 weeks and subsequently evaluated using manual palpation fusion scoring, microCT, and histological analysis.…”
Section: Methods Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, a negative control group was not used, as ACS alone has previously demonstrated a 0% fusion rate and thus serves as a historical control. 12,18 Radiographic fusion was evaluated 4 and 8 weeks postoperatively. Spines were harvested at 8 weeks and subsequently evaluated using manual palpation fusion scoring, microCT, and histological analysis.…”
Section: Methods Study Designmentioning
confidence: 99%
“…All harvested spines were manually palpated for evidence of successful fusion by 3 independent, blinded observers using a previously published scoring system, whereby 0 indicates no bridging bone, 1 indicates unilateral bridging, 2 indicates bilateral bridging, and 3 indicates bilateral bridging with abundant bone formation. 12,18 Individual scores for each specimen were then averaged. As with the human patient population, in which unilateral bridging constitutes successful fusion, spines with an average score ≥ 1.0 were considered successfully fused.…”
Section: Determination Of Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The presence of variability in its use is a refl ection of uncertainty regarding effectiveness and outcomes, and unawareness regarding costs. An evidence-based approach to cost-effective bone graft decision making would consider both cost and outcome, and be guided by the goal of optimizing value.…”
mentioning
confidence: 99%
“…3,4,[8][9][10] A paper in this issue of Journal of Neurosurgery: Spine may alleviate some of these fears. Mendoza et al 7 demonstrated that, in a rat spinal fusion model, vancomycin was not inhibitory to bone growth.…”
mentioning
confidence: 99%